Evaluation of pre-hospital administration of adrenaline (epinephrine) by emergency medical services for patients with out of hospital cardiac arrest in Japan: controlled propensity matched retrospective cohort study - Nakahara, Shinji (BMJ Publishing Group Ltd., 2013)
Objectives To evaluate the effectiveness of pre-hospital adrenaline (epinephrine) administered by emergency medical services to patients with out of hospital cardiac arrest. Design Controlled propensity matched retrospective cohort study, in which pairs of patients with or without (control) adrenaline were created with a sequential risk set matching based on time dependent propensity score. Setting Japan’s nationwide registry database of patients with out of hospital cardiac arrest registered between January 2007 and December 2010. Participants Among patients aged 15-94 with out of hospital cardiac arrest witnessed by a bystander, we created 1990 pairs of patients with and without adrenaline with an initial rhythm of ventricular fibrillation or pulseless ventricular tachycardia (VF/VT) and 9058 pairs among those with non-VF/VT. Main outcome measures Overall and neurologically intact survival at one month or at discharge, whichever was earlier. Results After propensity matching, pre-hospital administration of adrenaline by emergency medical services was associated with a higher proportion of overall survival (17.0% v 13.4%; unadjusted odds ratio 1.34, 95% confidence interval 1.12 to 1.60) but not with neurologically intact survival (6.6% v 6.6%; 1.01, 0.78 to 1.30) among those with VF/VT; and higher proportions of overall survival (4.0% v 2.4%; odds ratio 1.72, 1.45 to 2.04) and neurologically intact survival (0.7% v 0.4%; 1.57, 1.04 to 2.37) among those with non-VF/VT. Conclusions Pre-hospital administration of adrenaline by emergency medical services improves the long term outcome in patients with out of hospital cardiac arrest, although the absolute increase of neurologically intact survival was minimal.